Sensate bilobed flap for postelectric burn defect over the posterior aspect of the elbow joint - Sanjeev Kumar; Aditya Narayan Choudhary (Indian Journal of Burns, 2024)
The bones over the posterior aspect of elbow joint are subcutaneous, and can easily get exposed following complications of bursitis, degenerative joint disease and burns.Because of the difficulty in treating these wounds a variety of local muscle, musculocutaneous, fasciocutaneous, distant, and free flaps have been described. Fasciocutaneous flaps have the advantage of using regional tissue in a single stage. But the donor defects need to be skin grafted, producing an additional wound at the graft harvest site. We hearby present our experience of using a sensate bilobed flap innervated by branches of medial brachial cutaneous nerve for coverage of post electric burn defect over posterior aspect of elbow joint, where donor defect was amenable to primary closure.